Design and performance analysis of small-sized multiband microstrip patch antenna on custom-made biopolymer substrate - Ahsan, M.R.; Islam, M.T.; Ullah, M.H. (De Gruyter, 2016)
This paper presents a simple design analysis and performance evaluation of rectangular, slotted, microstrip feed patch antenna. The design processes are performed by employing the finite element method (FEM)-based commercial EM simulation software High-Frequency Structural Simulator (HFSS). The proposed multiband antenna is composed of a rectangular, slotted radiator formed with four arc slots and central square slot, reduced ground plane, and microstrip line for feeding. The patch antenna is excited through the standard 50 Ω RF transmission line, impedance-compliant SMA connector that is connected to the microstrip line. The optimal parametric dimensions from the numerical simulations are used for constructing the physical prototype on a custom-made, ceramic-filled biopolymer substrate of ϵr=10.0. Based on simulation results, the experimental data are collected, analyzed, and compared; the surface current distributions on the patch, gain, and radiation patterns are critically discussed. The measured results show the impedance bandwidths for S11 less than -10 dB are 712 MHz at 0.788 GHz band, 1.38 GHz at 3.34 GHz band, and 2.46 GHz at 8.01 GHz band. The good radiation pattern performances, almost stable gain over the bands, and appreciable bandwidths recommend the antenna for operating in RFID, WiMAX, and C/X-band applications.